Pengaruh Good Corporate Governance Terhadap Kinerja Keuangan Perusahaan Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2023-2024 - Ferdiansyah Ferdiansyah; Risa Nurmala Dewi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to examine the effect of Good Corporate Governance on the financial performance of banking sector companies listed on the Indonesia Stock Exchange (IDX) during the 2023–2024 period. The study employs secondary data obtained from the annual reports and financial statements of banking companies listed on the IDX for the 2023–2024 period. The sampling technique used is purposive sampling, resulting in a sample of 52 companies over two years of observation, yielding a total of 104 firm-year observations. Data analysis is conducted using a quantitative approach with SPSS version 26, applying panel data regression analysis. The results indicate that the audit committee does not have a positive effect on financial performance, while the board of commissioners has a significant effect on financial performance. Meanwhile, managerial ownership does not have a significant effect on financial performance.